NONVERBAL COMMUNICATION IN GUILLERMO DEL TORO’S MOVIE: “THE SHAPE OF WATER” - Syam, Syafril Efendy; Abdullah, Abdullah; Halim, Abd. (Journal of English Literature and Linguistic Studies, 2025)
This research is entitled Nonverbal Communication in Guillermo Del Toro's Movie: “The Shape of Water”. A movie, also known as a movie, is a form of visual storytelling that typically involves a series of images and sounds that are presented to an audience in order to convey a narrative or message. The purpose of this research is to examine the nonverbal communication in the "The Shape of Water" movie using Mark L. Knapp (2013), Ekman (2003), and Judee Burgoon (1970) theory. Duration of the movie is 02.03.00 and the researcher found the collected data by watching the movie and reading the script. This study is focused on three research questions, the first is what types of nonverbal communication used in the Guillermo del Toro’s movie “The Shape of Water”, the second is what are the functions of nonverbal communication in the Guillermo del Toro’s movie “The Shape of Water” and the third is what are the impacts of the nonverbal communication in the Guillermo del Toro’s movie “Shape of Water”. The research method used in this research is descriptive qualitative method. The results of this study shown that “The Shape of Water” movie contains a variety type of nonverbal communication fully equipped with the functions and impacts of them. The "The Shape of Water" movie contains a variety type of nonverbal communication, including kinesics (five extracts), haptics (three extracts), proxemics (two extracts), chronemics (four extracts), vocalics or paralanguage (two extracts), and artifacts (three extracts). The researcher also set up several important functions of nonverbal communication in the movie, including complementing verbal communication (six extracts), regulating interaction (three extracts), conveying emotions (two extracts), expressing social relationship (two extracts), and conveying cultural information (two extracts). The researcher also discovered several types of nonverbal communication impacts in the movie, including cognitive impact (two extracts), affective impact (three extracts), behavioral impact (two extracts), relational impact (two extracts), cultural impact (three extracts), gender impact (two extracts), and power and status impact (two extracts).